Measurement of Earmuffs Attenuation at High Audible Frequencies - KOZŁOWSKI, Emil; MŁYŃSKI, Rafał (Archives of Acoustics, 2017)
Standardised measurements of sound attenuation of hearing protectors are performed in the frequency range from 125 Hz to 8 kHz. However, noise present at many workplaces contains significant components at higher audible frequency. Therefore, the knowledge about noise attenuation with earmuffs in the audible frequency range above 8 kHz is also necessary for proper hearing protection. The aim of this study was to obtain values of the noise attenuation with 27 ommonly-used earmuffs models in the 1/3 octave bands of 10, 12.5 and 16 kHz. The measurements were conducted with a real ear at threshold (REAT) method with participation of subjects. The study showed that attenuation of earmuffs ranged from 24.7 to 42.8 dB, depending on model of earmuffs and frequency band. Furthermore, the measurements were performed with the use of acoustic test fixture which is designed especially for testing hearing protectors. Results obtained with the use of acoustic test fixture indicated that this measurement method can lead to values close to attenuation measured with participation of subjects. On the other hand, values obtained with the use of acoustic test fixture may differ average up to 14 dB from REAT method.